Managing seminomatous and nonseminomatous germ cell tumors. Issue 3 (May 2018) - Chahoud, Jad; Zhang, Miao; Shah, Amishi; Lin, Sue-Hwa; Pisters, Louis L.; Tu, Shi-Ming
Abstract : Purpose of review: In the present review, we summarize the recent developments in the management of germ cell tumors (GCTs). Recent findings: Treatment-related acute and late-onset toxicity remains a key challenge in the management of GCTs, with recent evidence showing that the adverse health outcomes of etoposide and cisplatin for four cycles in comparison to bleomycin, etoposide, and cisplatin for three cycles appear to be similar. Recent data showed that multidisciplinary clinic approach and management in experienced academic centers were associated with improved overall survival in GCT patients. There are currently multiple conventional-dose chemotherapy options for salvage therapy in patients with refractory or recurrent disease. In addition, more efficacious high-dose chemotherapy regimens continue to be developed. The role of salvage conventional-dose chemotherapy versus high-dose chemotherapy is currently being investigated prospectively. Recent reports suggested that brentuximab vedotin could be a potential salvage option for cluster of differentiation 30 positive refractory GCTs. On the other hand the results of the first phase II clinical trial investigating pembrolizumab in refractory GCTs were disappointing showing no clinical activity. Finally, deep exploration of the immune profile of GCTs using immunohistochemistry and gene expression profiling has identified that advanced GCT stage was associated with decreased T-cell and Natural killer-cell signatures, whereas T regulatory, neutrophil, mast cell, and macrophage signatures increased with advanced stage. Even though these results indicated that activated T-cell infiltration correlated with seminoma histology and good prognosis, and could be used in the future as a biomarker, this approach needs to be validated in a large cohort. Summary: Remaining challenges to be addressed include minimizing therapeutic toxicity, and improving outcomes in patients with refractory/recurrent GCTs.